Barrio Logan Case Study: Modern Environmental Injustice - Marco Nunez Moctezuma; Gabriela Fernandez (Medical Sciences Forum)
Barrio Logan is a Mexican American community in San Diego in which industrial companies and residences share a space enclosed by a bay and an interstate. Ever since WWII, the Barrio Logan community has faced environmental injustice. There is a gap in Barrio Logan’s ability to self-monitor, so business models were developed to bring forth citizen science projects based on data collected from government environmental studies, the nurse’s office at Barrio Logan’s Perkins K-8 School, and interviews with Perkins K-8 School’s principal and the director and staff at the Chicano Park Museum and Cultural Center. It was found that children in Barrio Logan are experiencing a health crisis. Homelessness, single-parent households, unemployment, gentrification, low-wage jobs, continuous diesel particulate matter exposure, and high levels of asthma can be found in Barrio Logan. There is a lack of easily accessible, community-wide health programs that address ACEs and a lack of air pollution monitoring.